MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB PADA MASA PANDEMI DI SMP MUHAMMADIYAH 7 SURAKARTA - Nur Safitri; Nurul Latifatul Inayati; Zaenal Abidin (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
This study discusses how students' interest in learning Arabic at SMP Muhammadiyah 7 Surakarta during the pandemic. This research to aim about the development of students' interest in learning Arabic at SMP Muhammadiyah 7 Surakarta. Researchers used this type of field research located at SMP Muhammadiyah 7 Surakarta using a phenomenological qualitative approach. The subjects of this study were the curriculum and Arabic teachers, while the object of this study was the students' interest in learning Arabic during the pandemic. The method of data collection is carried out by interviewing, observation of learning through Googlemeet, documentation and data analysis using data reduction techniques, data presentation, then drawing conclusions. The researcher got the result that Arabic is very less attractive to students for them to learn or practice in their daily life, coupled with the state of the Covid-19 pandemic which caused school institutions to require online learning. Thus attention from parents is also needed so that students are able to participate in online learning at home properly, because the teacher can only monitor students when they take part in online learning via Googlemeet and do assignments through Google Classroom and WhatsApp